2003
DOI: 10.1002/chem.200304877
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic, Reactivity, and Structural Studies on Half‐Sandwich (η5‐C5Me5)Be and Related Compounds: Halide, Alkyl, and Iminoacyl Derivatives

Abstract: The half-sandwich compounds [(eta(5)-C(5)Me(5))BeX] (X=Cl, 1 a; Br, 1 b), readily prepared from the reaction of the halides BeX(2) and M[C(5)Me(5)] (M=Na or K), are useful synthons for other (eta(5)-C(5)Me(5))Be organometallic compounds, including the alkyl derivatives [(eta(5)-C(5)Me(5))BeR] (R=Me, 2 a; CMe(3), 2 b; CH(2)CMe(3), 2 c; CH(2)Ph, 2 d). The latter compounds can be obtained by metathetical exchange of the halides 1 with the corresponding lithium reagent and exhibit NMR signals and other properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…The chemistry of beryllium compounds was mainly developed in the 1960s, but is getting rising attention in the last decade 18. Many neutral and anionic beryllium compounds are known, but the preparative chemistry of cationic Be complexes is by far less developed.…”
Section: Introductionmentioning
confidence: 99%
“…The chemistry of beryllium compounds was mainly developed in the 1960s, but is getting rising attention in the last decade 18. Many neutral and anionic beryllium compounds are known, but the preparative chemistry of cationic Be complexes is by far less developed.…”
Section: Introductionmentioning
confidence: 99%
“…58 No hydride resonance could be found in the 1 H NMR spectrum, however, and 1 H, 9 Be, and 13 C{ 1 H} NMR indicated that the only products were a mixture of 10 and unreacted (C 5 Me 5 )BeBr. 58 No hydride resonance could be found in the 1 H NMR spectrum, however, and 1 H, 9 Be, and 13 C{ 1 H} NMR indicated that the only products were a mixture of 10 and unreacted (C 5 Me 5 )BeBr.…”
Section: Hydridesmentioning
confidence: 97%
“…Three isomers have been isolated 58 ; at À78 C, isomer C is formed exclusively and reversibly, suggesting that it has the lowest barrier to C-C coupling reactions. It has four possible isomers if both the Z 5 /Z 1 -and the "molecular inversion" rearrangements that are proposed to occur in Cp 2 Be are operative (Scheme 2, A-D).…”
Section: Beryllium Monocyclopentadienylsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyclopentadiene and its derivatives have received a great deal of attention as ligands for alkaline earth and d and f transition metals. [1][2][3][4][5][6][7][8] Their ligand capabilities are closely related to the aromatic character of the five-membered ring when it captures an extra electron and becomes a 6p-electron system. The aromaticity of the cyclopentadienyl anion is also responsible for the significant acidity of cyclopentadiene, both in the gas phase and in solution.…”
Section: Introductionmentioning
confidence: 99%